Analysis Of The Effect Of Digital Transformation On Smes Around Unimed - Mica Siar Meiriza; Abim Khaffi Maulana; Enzi Anatasya Sembiring; Etri Br Kaban; Salamah Tumangger (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
From a global viewpoint, the business climate is unpredictable and competitive due to external causes, the majority of which are technological change generators. The purpose of this study is to determine the impact of technology on SMEs in the city of Medan. The samples were gathered from small and medium-sized firms (SMEs) in the UNIMED area. With a qualitative design, this study collects data through semi-structured interviews with eight enterprises in the UNIMED area. Interviews were transcribed following data collection to identify common themes. This study highlighted themes such as "getting exposure" and "getting effective sales figures" as a result of implementing digital transformation, as expressed by six of the eight participants. The findings show that. Digital transformation has a tremendous impact on consumer interactions and the simplicity of shopping. The data also suggest that online sales and digital marketing are the most popular digital platforms, with some SMEs in UNIMED effectively implementing them.The aim of this research is to determine the influence of digital transformation on SMEs by taking a sample 8 businesses around UNIMED and how effective digital influence is on business progress. From the results obtained, digital transformation has a significant influence even though it also experiences challengs. 6 of the 8 businesses studied said that rapid technological chenge is also a chellenge that must be taken into account and the advantage that these SMEs gain is that customers who are far away can also reach them. The business is only digital without having to come directly to the place. Finally, the report identifies digital maintenance and rapid technological development as challenging considerations.